Study on Laparoscopic versus Open Appendectomy: A Hospital Based Study - Ahmed, J; Ahmad, S S; Al Abdulghani, Asmaa M HS; Mir, S A; Akhter, S; Jehan, Nusrat (Asian Journal of Medical Research, 2018)
Background: The putative advantages of the laparoscopic approach are quicker and less painful recovery, fewer postoperative complications and better cosmesis. It allows better assessment of other intra-abdominal pathologies. Subjects and Methods: A total of 56 patients were included in the study during this period, according to the inclusion and exclusion criteria. Out of this 56 patients, 28 underwent an open appendicectomy, 28 underwent a laparoscopic appendectomy. Results: Average age of patients undergoing LA was 24.3 years while it was 26.2 years for those undergoing OA. The operative duration was initially longer in the LA group as compared to that in the OA group but with the learning curve it decreased to less than that of OA; The use of analgesics, average hospital stay and return of bowel movements was better in case of LAas compared to OA. Conclusion: The Laparoscopic appendectomy is equally safe, and can provide less postoperative morbidity in experienced hands, as open appendectomy.